FINANCIAL INCLUSION IN PERUVIAN DISTRICTS: MULTIDIMENSIONAL APPROACH AND DE-TERMINING FACTORS - Zamalloa, Juan Carlos (2016)
The research explains why factors such as the level of family assets, infrastructure, education and distance to the capital district determine financial inclusion in the districts of Peru. Based on this objective, a descriptive analysis was performed on the relationship between the variables and the approximation on the inferential analysis: estimation using Ordinary Least Squares of a cross section with data up to December 2015.The results show a positive relationship between the factors, with the exception of distance, which could be explained by a concentration in the provision of financial services. Whereas, a large portion of the financial inclusion at the district level would be explained by other components.By identifying these other components, a broader multidimensional definition of financial inclusion was outlined, approaching the issue from a dynamic and evolutionary perspective, understanding that the economic phenomenon is not a static situation or an end, but a process that constantly changes on the basis of the decisions of economic agents, besides there is a coexistence between formal and informal services, which feed each other.